What does onomastics study, and what does it serve? Some reflections in the context of the New Humanities - Rutkowski, Mariusz (Papers in Linguistics, 2021)
The article considers the place of onomastics within the humanities research. It is shown that the linguistic status of proper names does not only determine the linguistic description of science. The aims and social benefits of names-related research are also considered. In the light of the so-called New Humanities, the potential of onomastics manifests itself, consisting in revealing hidden ideologies that influence the shape of social structure. On the basis of research on personal names, such categories as class and unequal access to power, cosmopolitanism, globalisation or nationalism may emerge or be highlighted. The study of geographical names, in turn, may point to the influence of nationalism or ethnocentrism, as well as enforced anti-communism. The opportunities offered by engaged (critical) onomastics outlined in the article suggest a great potential of this field of research in relation to other fields of science as well as society itself.